Crystal structure of 3,5-bis((E)-4-methoxy-2-(trifluoromethyl)benzylidene)-1-methylpiperidin-4-one, C24H21F6NO3 - Zhou Xia; Sun Zhong-Hao; Shan Guang-Zhi; Meng Qing-Guo (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C24H21F6NO3, monoclinic, P21/c (no. 14), a = 16.0076(10) Å, b = 7.7424(4) Å, c = 17.3259(11) Å, β = 96.161(5)°, V = 2134.9(2) Å3, Z = 4, R gt(F) = 0.0563, wR ref(F 2) = 0.1517, T = 100.0(1) K.